Comparison of Sleep Quality in Athlete and Non-Athlete Pregnant Women - Marzieh Sadat Azarniveh; Seyed Alireza Tavakoli Khormizi (Golestan University of Medical Sciences, 2017)
Background: Recent studies have shown that physical activity is an effective factor in improving sleep quality. Therefore, this study aimed to compare the sleep quality of athlete and non-athlete pregnant women. Methods: This cross-sectional descriptive analytical study was performed on 300 pregnant women in the last trimester of pregnancy, referred to prenatal care unit of Amiralmomenin Hospital in city of Zabol. After selection via convenience sampling, participants were divided into two groups of athletes and non-athletes based on their level of physical activity. Data were collected via a demographic form and Pittsburgh sleep quality and Baek physical activity questionnaires. Data was analyzed using descriptive statistics and t-test. Results: The mean score of sleep quality in pregnant women was 8.51 ± 2.09. Overall, 81.2% of the subjects had poor sleep quality. The sleep quality of athlete (7.19 ± 1.68) and that of non-athlete (10.18 ± 2.28) pregnant women were undesirable. However, athlete pregnant women had significantly better sleep quality compared to non-athletes (P=0.003). Conclusion: Based on the results and the high prevalence of sleep disorders in pregnant women, as well as the positive impact of physical activity on sleep quality, daily physical activity seems essential for improvement of sleep quality in pregnant women.